Cyclic Prefix (CP) jamming against eavesdropping relays in OFDM systems - Solaija, Muhammad Sohaib J.; Madni, Haji Muhammad Furqan Ahmed; Ankaralı, Zekeriyya Esat; Arslan, Hüseyin (IEEE-Institute of Electrical and Electronics Engineers Inc., 2022)
Cooperative communication has been widely used to provide spatial diversity benefits for low-end user equipments, especially in ad hoc and wireless sensor networks. However, the lack of strong authentication mechanisms in these networks leaves them prone to eavesdropping relays. In this paper, we propose a secure orthogonal frequency division multiplexing (OFDM) transmission scheme, where the destination node transmits a jamming signal over the cyclic prefix (CP) duration of the received signal. Simulation results verify that as long as at least a part of the jamming signal falls to the actual data portion of the eavesdropping relay, it spreads through all the data symbols due to the fast Fourier transformation (FFT) operation, resulting in degraded interception at the eavesdropper.
Keywords: 5G; 6G; Cyclic Prefix (CP); Jamming; OFDM; Physical Layer Security (PLS)